Development and validation of a screening instrument to assess the types and quality of foods served at home meals - Fulkerson Jayne A; Lytle Leslie; Story Mary; Moe Stacey; Samuelson Anne; Weymiller Audrey (BMC, 2012)
Abstract Background Although there is growing interest in assessing the home food environment, no easy-to-use, low cost tools exist to assess the foods served at home meals, making it difficult to assess the meal component of the food environment. The aim of this study was to develop and validate a user-friendly screener to assess the types of foods served at home meals. Methods Primary food preparing adults (n = 51) participated in a validation study in their own homes. Staff and participants independently completed a screener as participants cooked dinner. The screener assessed the types of foods offered, method(s) of preparation, and use of added fats. Two scale scores were created: 1) to assess offerings of foods in five food groups (meat and other protein, milk, vegetables, fruit, grains), 2) to assess the relative healthfulness of foods based on types offered, preparation method, and added fats. Criterion validity was assessed comparing staff and participant reports of individual foods (kappa (k)) and scale scores (Spearman correlations). Results Criterion validity was high between participants' and staffs' record of whether major food categories (meat and other protein, bread and cereal, salad, vegetables, fruits, dessert) were served (k = 0.79-1.0), moderate for reports of other starches (e.g., rice) being served (k = 0.52), and high for the Five Food Group and Healthfulness scale scores (r = 0.75-0.85, p < .001). Conclusions This new meal screening tool has high validity and can be used to assess the types of foods served at home meals allowing a more comprehensive assessment of the home food environment.